BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN NIAT MEROKOK SISWA SMP DI KOTA SEMARANG - Rafiah Al Qodri; Syamsulhuda BM; Emmy Riyanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Smoke is cause of death large preventable in the world. In 2013 the number of smokers in Indonesia reached 53,860,457 . As many as 3.9 million children aged 10-14 years who has been active smokers this figure increased by 80 % within 9 years. The number of smokers in semarang city of 17,8 %, the first smoking at the age of 10-14 year by 18 %. The main purpose of this research is to analyze several factor related the intention smoking among junior highschool students in semarang city . The method used in this research is descriptive analytic with cross sectional study approach.The populations are 6 junior highschool in southern Semarang and Gunung Pati with multi stage sampling technique was obtained 100 sampels. The analysis data uses univariate, bivariate with chi-square statistical test with 95% of significance level, and multivariate regression test. 52% of respondents have intentions to smoke. Variables that have a significant impact are gender (p-value = 0.000 <0.05) and OR = 5.306. The results of the bivariate analysis there is a correlation between the sexes (p = 0.000), subjective norm friend (p = 0.004), and pocket money (p = 0.003) with the intention of smoking. And there is no correlation between age (p = 0.092), exposure to PHW (0,266), attitude (p = 0.296),  subjective norm parents (p = 0.118), subjective norm teachers (0.156). Is suggested that students be selective and careful in choosing friends and society. parents and other family members not to smoke at home so as to give a positive example to their children.